Environmentally friendly optical multi-color rewritable paper based on inverse photonic glass. (October 2022) - Wang, Zhenzhi; Zhang, Shufen; Tang, Bingtao
Abstract: As a substitute for traditional disposable paper, rewritable paper has been widely studied in recent years because of its low consumption. However, it is still a major challenge for rewritable paper to meet the requirements of simple large-area preparation, biocompatibility, good cycle stability and multi-color output. In this study, a new type of rewritable paper with silk-fibroin inverse photonic glass (SF-IPG paper) is developed. The simple spray coating method is used to realize the rapid and large-area preparation of it. Based on the regulation of the structure of inverse photonic glass, through the dynamic hydrogen bonding between H2 O and silk fibroin polymer chains, the multi-color text output of SF-IPG paper written with a water pen is realized. SF-IPG paper has good mechanical strength, excellent biocompatibility, high structural stability and unique water response mechanism. At the same time, it is simple to produce, fully meets the requirements of environmental protection and sustainable development. Therefore, this preparation strategy has broad application prospects in the field of rewritable paper. Highlights: The hierarchical control of the microstructure of silk fibroin films is realized, and the mechanisms of structural transformation is first put forward. Inverse photonic glass structure with hard to copy characteristics is first applied to rewritable paper. The spray coating method is used to make the rewritable paper, which lays a foundation for the industrial scale production. The rewritable paper exhibits good mechanical strength, high structural stability and rich optical modes.